ADDIE-BASED WEB BOOKING SYSTEM FOR RURAL TOURISM - Maulana, Firman; Fahmi, Hairul; Akbar, Jihadul (Jurnal Informatika dan Rekayasa Elektronik, 2025)
Digital transformation plays a crucial role in fostering innovation within community-based tourism services, particularly in rural areas of Indonesia. This study aims to develop a Web-Based Travel and Car Booking Application using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) as a systematic framework to support the digital transformation of tourism transportation services in Rembitan Village, Central Lombok Regency. A mixed-method approach was employed to integrate user needs analysis, user-centered design, system development, and functional evaluation. The black-box testing results indicated that all system modules operated according to specifications with a 100% success rate. A quantitative evaluation using the System Usability Scale (SUS) was conducted on ten key participants, representing the entire population of active transport operators in the village. The results yielded an average score of 91.5 (Excellent category), indicating high usability and ease of use for non-technical users. Qualitative findings revealed improvements in operational efficiency, faster booking and payment confirmation, and greater transparency through the integration of the WhatsApp API and AI Chat Integration modules. The findings confirm that the ADDIE model effectively produces a digital system that is scientifically rigorous, technically reliable, and socially impactful. The developed application serves as a practical prototype for Smart Tourism Village implementation, promoting sustainable digital transformation and local economic empowerment within rural tourism sectors in Indonesia.